Quantification of Genetically Modified Maize in Animal Feed Using Real-Time Polymerase Chain Reaction - Kesar Singh, Jasbeer Kaur (2011)
More generally modified organisms (GMOs) are being develop and approved wordwide resulting in more GM crops being incoporated into livestock production systems. The presence of a foreign gene in the crop has raised concern of safe feed and safe foods of animal origin such as meat milk and eggs which are significant sources of high-quality food for humans. Therefore identifiying rapid and economical DNA-based GMO analytical method for screening feed and food ingredients is imperative. In Malaysia there is no comprehensive data on the testing and presence of GMOs in food which are currently not regulated. The objective of the study is to identify suitable DNA extraction method from feed as well as detect and quantify GM maize events. In Malaysia such a study has never been undertaken before. In attempting to identify suitable DNA extraction method for feeds (coarse mix, pellet or extruded feed) from seven different DNA extraction methods (Roche, Qiagen, NucleoSpin, Epicentre, Wizard, CTAB and modified CTAB methods), DNA qualiry in terms of the amplication ability of copy maize endogenous hmg (high mobility group) gene was compared using real-time polymerase chain reaction (PCR) technique. relative levels of hmg were used to evaluat the DNA quality. DNA was also assessed in terms of yeild purity and interity. Further in the the study, four GM maize events (event MON810,MON863,NK603 and GA21) were analyzed in 103 feed and 20 maize extracted using theRoche automated system which uses the proprietary glass magnetic particles to bind DNA. Except for GA21 which is not approved for import in Malaysia events MON810, MON863 and NK603 are approved. The fiding illustrate that the genomic DNA extraction methods have significant influnce on DNA yield purity, integrity and quality. The Epicentre method extracted significantly the highest DNA yield followed by the modified CTAB method . The Roche and Wizard methods had significantly DNA yeild but high DNA purity. All six methods except Wizard produced low molecular weight DNA indicating highhly fragmented DNA dua to food processing. The Wizard method was the only method that produced high molecular weight DNA depite having the lowest yeild. Finally the Wizard method also recovered the most amplifiable DNA per reaction indicating highest DNA quality. For the first time in Malaysia a total of 103 feed and 20 maize samples were used to obtain an overview of the incidence of GMO presence in foods and raw maize GM material was present in 26.2% feeds and 65% maize samples. Single-event and multiple-events were identified in the GM samples with 50% of the GM samples containing multiple-events. All GM samples contained MON810 (100%) followeds by NK603 (47%), GA21 (25%) and MON863 (2.5%). Surprisingly, the non-approved GA21 was detected more than the approved event MON863. Concentrations of GMs were also significantly higher for the unprocessed maize compared to the processed feeds. This study which represents a fast and reliable methodology providess an insight on Malaysia scenario and will serve as important baseline data in future policies to regulate GMOs.